Side Effects of Yttrium-90 Radioembolization - Riaz, Ahsun; Awais, Rafia; Salem, Riad (Frontiers in Oncology, 2014)
Limited therapeutic options are available for hepatic malignancies. Image guided targeted therapies have established their role in management of primary and secondary hepatic malignancies. Radioembolization with yttrium-90 (90Y) microspheres is safe and efficacious for treatment of hepatic malignancies. The tumoricidal effect of radioembolization is predominantly due to radioactivity and not ischemia. This article will present a comprehensive review of the side effects that have been associated with radioembolization using 90Y microspheres. Some of the described side effects are associated with all transarterial procedures. Side effects specific to radioembolization will also be discussed in detail. Methods to decrease the incidence of these potential side effects will also be discussed.